Antibodies against 12 infectious agents in free-ranging Eurasian beaver (Castor fiber L.) from the Czech Republic - Sedlák, Kamil; Vodička, Roman; Bártová, Eva; Budíková, Marie; Vorel, Aleš (Acta tropica, 2025)
In recent years, populations of beavers are rising and spreading in Europe, so we can expect increasing human contact with them in future. The aim of the study was to examine the blood samples of free-ranging beavers to detect antibodies to 12 infectious agents. In total, the blood samples from 76 free-ranging Eurasian beaver (Castor fiber L.) were used for the detection of antibodies to 12 infectious agents, including 3 parasites (Toxoplasma gondii, Neospora caninum, Trichinella spp.), 5 bacteria (Brucella spp., Chlamydophila abortus, Coxiella burnetti, Francisella tularensis, Leptospira spp.), and 4 viruses (Aujeszky's Disease Virus ADV, Hepatitis E virus HEV, Tick-borne Encephalitis virus TBEV, and West Nile Fever virus WNV). The sera were examined by Agglutination test, or Enzyme-linked immunosorbent assay, depending on the tested pathogen. Out of 76 animals, the following seropositivity was obtained: T. gondii 18.4 % (14/76), N. caninum 7.9 % (6/76), Leptospira spp. 3.9 % (3/76), F. tularensis 2.6 % (2/76) and Hepatitis E virus 2.6 % (2/76), with statistically significant differences in the positivity of animals to different pathogens (p=0.0007). Antibodies to the other 7 agents were not found. In total, 19 of 76 (25 %) animals had antibodies at least to one tested pathogen, with single infection in 12 animals (15.8 %) and mixed infection of 2-3 agents in 7 animals (9.2 %). There was no difference in positivity between individuals' genders (24.2 % for females and 23.7 % for males, p=0.7244), age of animals (juvenile 15.4 %, subadults 20 %, adults 31.6 %, p=0.3962), area (South Moravia 31.9 %, Český les 28.6 %, Elbe (Labe) River 14.3 %, and Šumava National Park 0 %, p=0.1894) and year of sampling (from 9 positive samples in 2008 to 0 positive samples in 2010). This first seroepidemiological study, dedicated to a wide range of pathogens, determined the extent to which this animal species is infected with these pathogens.
Keywords: Leptospirosis; aglutinační testy; Rodentia; bakteriální infekce; Female; Toxoplasmosis; Tularemia; protilátky bakteriální; ELISA; Virus Diseases; séroepidemiologické studie; Serology; virové nemoci; zvířata; Enzyme-Linked Immunosorbent Assay; Neosporosis; Antibodies, Bacterial; Wildlife; ženské pohlaví; Male; protilátky protozoální; Czech Republic; hlodavci; Agglutination Tests; protilátky virové; Antibodies, Protozoan; Antibodies, Viral; Bacterial Infections; Animals; Česká republika; mužské pohlaví; Seroepidemiologic Studies